Effect of the change of climate indicators on agricultural yields in Son La province - Hung, Nguyen The; Quyen, Nguyen Huu (Vietnam Journal of Science and Technology, 2017)
Due to climate change, the agro-climatic indicators in Son La province has changed in the following trends: (i) the total heat in the Winter - Spring crop and the Summer crop as well as the total annual heat have increased; (ii) The amount of time in a year with temperature below 20 degrees has shortened; the amount of time in a year with temperatures above 25 degrees has lengthened; (iii) the absolute minimum temperature tends to increase rapidly; (iv) the rainfall in Winter - Spring crop has increased slightly whereas the season rainfall and total annual rainfall tend to decrease. The climatic factors in Son La province obviously affect rice yield in the Winter - Spring crop, the Summer crop as well as corn and soybeans. However, compared with other crops, soybean yield is less related to climatic factors. There are major differences in climate characteristics between the high and the low crops yield year. However, these differences depend on the type of the crop and the harvest season.